Paradoxical Association Between Dietary Lifestyle and Cardiovascular Risk: Cross-Sectional Analysis of Patient Responses from A Tertiary Care Hospital: Pharmaceutical Science-Pharmacy practice - T, Sumathy; V .P, Maheshkumar; S, Jaikumar (International Journal of Life Science and Pharma Research, 2022)
A decrease in cardiovascular event risk with a decrease in total and LDL – cholesterol level is termed as “cholesterol paradox” or “risk factor reversal”. Cardiovascular risk does not have a linear relationship between LDL – cholesterol levels, and other substantial risk factors of cardiovascular events are being disregarded. The aim of this study is, to identify modifiable risk factors of cardiovascular events other than those well proved to cause dyslipidemia. A cross-sectional study was conducted with 652 participants in a tertiary care hospital. Patients were grouped into two, based on the history of cardiovascular events. Demographics and patient responses captured using pre-validated questionnaires were analyzed. 5mL blood samples were collected by venipuncture and lipid profile was estimated. Association between cardiovascular events and explanatory variables. was determined using Chi square test and Odds ratio at 95% confidence intervals. Higher risk of CV events was found among smokers 0.232 [0.144 – 0.373]. Consumption of white sugar, refined oil, processed cold beverages and fast food products increased CV risk respectively. Moreover, total cholesterol, LDL-C and triglycerides were found to decrease after one year of counselling the patients. The classical hypothesis of dyslipidemia induced atherosclerosis may not be the predominant cause of CV events. Herein, we report no association between high fat diet and CV risk while we observed higher risk in consumers of refined and ultra processed food products. However, significant control of cholesterol was observed in patients who shifted to Unrefined food products.